Death due to Aortobronchial Fistula Related Massive Hemoptysis a Case Report - Özsoy, Sait; Alkan, Hanife Alkurt; Pehlivan, Sultan; Gökmen, Asude; Akçan, Ramazan; Alkan, Metin (The Bulletin of Legal Medicine, 2016)
Aortobronchial fistulas are relatively rare but usually fatal if not treated since they might cause massive hemoptysis. Here we present a case of death of a 17-year-old male due to massive hemoptysis secondary to aortobronchial fistula. The deceased was firstly admitted to an emergency department with dyspnea, tachypnea, tachycardia, resistant metabolic acidosis, confusion, and somnolence. He was diagnosed with “diabetic ketoacidosis” following examinations; however, detailed radiological and clinical investigations revealed community-acquired infection findings and medical treatment was started accordingly. He was discharged after 15 days of hospitalization; however, he died unexpectedly 12 days after discharge.At autopsy a 4-cm aortobronchial fistula was found between the thoracic aortic wall and the left main bronchus. Histopathological examination of fistula showed diffuse and intense necro-inflammatory reaction and inflammatory response with polymorphonuclear leukocytes and necrosis. Death was attributed to massive hemoptysis and blood aspiration due to aortobronchial fistula.A feedback system, towards healthcare centers, based on autopsy findings and exact cause and mechanisms of death will contribute improvement of diagnosis and treatment approach.Keywords: Aortopulmonary fistula; Respiratory Tract Fistula; Bronchial Fistula; Vascular Fistula; Hemoptysis; Cannabinoids; Autopsy.
Keywords: aortopulmonary fistula; respiratory tract fistula; bronchial fistula; vascular fistula; hemoptysis; cannabinoids; autopsy